Ultimate Wolverine. Vol. 2, Logan - Condon, Chris (Comics writer) (Marvel Worldwide, Inc., 2026)
"The Opposition may have finally helped Logan reclaim his identity! But to what lengths will Colossus, Magik and Omega Red go to keep their prized weapon? Don't miss Ultimate Magik revealing the shocking extent of her power! But as the Opposition infiltrates a facility holding a group of high-powered mutants, the Winter Soldier's handler has a sinister plot to destroy them once and for all."--